Council Size Matters: Filling Blanks in Women's Municipal Representation in New Jersey. (December 2018) - Kjaer, Ulrik; Dittmar, Kelly; Carroll, Susan J.
This article "goes local" to investigate the representation of women on city councils, seeking explanations for the variation in women's descriptive representation at the municipal level. Using the State of New Jersey (NJ) as a case, it is asked: what explains why women fare electorally better in some NJ municipalities than in others? More specifically, what explains "blanks"—or councils on which women are absent—in women's representation in local politics? It is demonstrated that council size is a significant predictor of women's presence or absence, but not percentage representation, on city councils.